Optimalisasi Jumlah Bibit dan Dosis Pupuk Organik Magau terhadap Pertumbuhan dan Hasil Padi (Oryza sativa L.) Varietas Inpari 32 - Auliya, Auliya; Lukman, Lukman; Adnan, Adnan (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2025)
This study aimed to determine the effect of the number of seeds per planting hole and the dose of magau organic fertilizer on the growth and yield of Inpari 32 rice variety. The study was conducted in Ginunggung Village, Tolitoli Regency, Central Sulawesi, from December 2023 to May 2024 using a 2×3 factorial Randomized Block Design (RAK) with 27 experimental units. The results showed a significant interaction between the number of seeds and organic fertilizer on plant height at 15 days after planting and wet grain weight, with the best combination at 7 seeds per planting hole and a fertilizer dose of 2 kg (20 tons/ha). The number of seeds significantly affected plant height, number of tillers, number of panicles, and wet grain weight, while magau organic fertilizer significantly affected plant height, number of tillers, and dry grain weight. Several other parameters, such as panicle length, number of filled and empty grains, grain weight per plot, and 1,000-grain weight, did not show a significant effect.